New insights into the red and green pigments in the illuminated foral charter of Setubal (1515) by combined use of μ-Raman and X-ray fluorescence spectrometry - Guerra, Mauro (2019)
SPTDC/EAT-EAT/112662/2009 SFRH/BPD/94234/2013